Gut microbiota profiles and fecal beta‐glucuronidase activity in kidney transplant recipients with and without post‐transplant diarrhea. Issue 5 (9th March 2021) - Zhang, Lisa T.; Westblade, Lars F.; Iqbal, Fatima; Taylor, Michael R.; Chung, Alice; Satlin, Michael J.; Magruder, Matthew; Edusei, Emmanuel; Albakry, Shady; Botticelli, Brittany; Robertson, Amy; Alston, Tricia; et al.
Abstract: Post‐transplant diarrhea is a common complication after solid organ transplantation and is frequently attributed to the widely prescribed immunosuppressant mycophenolate mofetil (MMF). Given recent work identifying the relationship between MMF toxicity and gut bacterial β‐glucuronidase activity, we evaluated the relationship between gut microbiota composition, fecal β‐glucuronidase activity, and post‐transplant diarrhea. We recruited 97 kidney transplant recipients and profiled the gut microbiota in 273 fecal specimens using 16S rRNA gene sequencing. We further characterized fecal β‐glucuronidase activity in a subset of this cohort. Kidney transplant recipients with post‐transplant diarrhea had decreased gut microbial diversity and decreased relative gut abundances of 12 genera when compared to those without post‐transplant diarrhea (adjusted p value < .15, Wilcoxon rank sum test). Among the kidney transplant recipients with post‐transplant diarrhea, those with higher fecal β‐glucuronidase activity had a more prolonged course of diarrhea (≥7 days) compared to patients with lower fecal β‐glucuronidase activity (91% vs 40%, p  = .02, Fisher's exact test). Our data reveal post‐transplant diarrhea as a complex phenomenon with decreased gut microbial diversity and commensal gut organisms. This study further links commensal bacterial metabolism with an important clinical outcome measure, suggesting fecal β‐glucuronidase activity could be a novel biomarker for gastrointestinal‐related MMF toxicity.